The results of analysis of design, structuring and implementation of physics course for technical university students; 10th International Technology, Education and Development Conference (INTED2016) - Sklyarova E. A. Elena Aleksandrovna; Semkina L. I. Lyudmila Iosifovna; Lider A. M. Andrey Markovich; Smekalina T. V. Tatiana Vladimirovna; Kudiyarov V. N. Victor Nikolaevich; Chudinova E. A. Ekaterina Aleksandrovna (2016, 2016)
Title screen